From Perceived Supervisor Social Power to Employee Commitment: Definition and Scale Development - Chénard-Poirier, Léandre Alexis; Vandenberghe, Christian; Morin, Alexandre J. S. (Frontiers in Psychology, 2021)
This article reports the results of a multi-study examination of the reliability and validity of a measure of perceived supervisor social power (PSSP), which refers to employees’ perceptions of a supervisor’s potential to influence important organizational actors and organizational decisions. The proposed 5-item measure of PSSP was found to be invariant across four samples (grouped in three studies) drawn from countries that substantially differ on power distance: France (N = 350), Canada: French-speaking respondents (N = 271), Canada: English-speaking respondents (N = 462), and Romania (Time 1 N = 244 and Time 2 N = 152). Study 1 and Study 2 showed that PSSP was positively related to affective organizational commitment. All three studies showed that PSSP acted as a positive moderator of the relation between affective commitment to the supervisor and affective organizational commitment. PSSP was also related yet distinct from, French and Raven’s (1959) five power bases (Study 2), and the related constructs of perceived supervisor networking ability, supervisor perceived organizational support, and perceived supervisor-organization value congruence (Study 3). Implications of these findings for future research on supervisor social power are discussed.